Decentralized finance (DeFi) markets for startups: search frictions, intermediation, and the efficiency of the ICO market - Paul P. Momtaz (Small Business Economics, 2024)
Abstract This paper examines the efficiency of the Initial Coin Offering (ICO) market through a search-theoretical lens. Search intensity associated with the process of identifying valuable startups is increasing in market granularity. DLT increases market granularity because asset tokenization lowers entry barriers. Lower-end entrants, however, increase aggregate search intensity but may lack search skills. The resulting search-related inefficiency creates a niche for intermediaries or institutional investors that specialize on search. Consistent with the theory, specialized crypto funds increase ICO market efficiency by reducing search frictions, inter alia, by shortening the time-to-funding and increasing the funding amount. At the same time, crypto funds extract sizable economic rents for their intermediation services. Overall, the study relates to the general trade-off between centralization and decentralization in entrepreneurial finance. It suggests that market frictions specific to early-stage crowdfunding of entrepreneurship may prevent “perfectly” Decentralized Finance (DeFi) markets from functioning efficiently.
Additional information: G23;G24;L26
Keywords: 330; Entrepreneurial finance; Blockchain-based crowdfunding; Initial Coin Offering (ICO); Tokenization; Crypto funds; Decentralized Finance (DeFi)